"Dominion status": History, framework and context. (21st January 2020) - Oliver, Peter C
Abstract: This article attempts to explain "Dominion status" by various means. First, it notes that the word "Dominion" has had different meanings over time, even though it is most closely associated with the status acquired by Australia, Canada, Ireland, Newfoundland, New Zealand, and South Africa in the years 1926 to 1931. Second, Dominion status from 1926 to 1931 is compared to the constitutional claims made a century and a half earlier by American colonists. Third, Dominion Status as of 1931 is explained by way of comparison with what came before, paying particular attention to issues of repugnancy, extraterritoriality, reservation and disallowance. And, finally, this article observes the importance of constitutional conventions throughout.